Analisis Kebutuhan Lembar Kerja Peserta Didik Sistem Pencernaan Berbasis Model Problem Based Learning Terintegrasi Nilai Islam Kelas XI MA - Harahap, Ummi; Ardi, Ardi (LP2M IAIN Ambon, 2025)
This study aims to determine the need for learning media in the form of student worksheets on the digestive system based on an integrated problem-based learning model with Islamic values for grade XI MAN 1 Padang Lawas Plus Skills & Research. This study is a quantitative descriptive study. The method used to collect data was through the distribution of questionnaires to biology teachers and grade XI MIPA students. The results of the analysis of the student and teacher questionnaires indicate that the digestive system material is one of the materials considered challenging in learning, and the learning resources used so far are deemed uninteresting. The integration of Islamic values in these worksheets aims to connect biological concepts with the Quran and Hadith, thereby making learning more meaningful and fostering Islamic character development in students. The learning resources provided by teachers include biology textbooks, PowerPoint presentations, simple worksheets, and others; however, student learning outcomes remain consistent, highlighting the need for varied learning media. One solution to this issue is to develop learning media in the form of student worksheets based on the problem-based learning model integrated with Islamic values, which are valid and practical.